Assessment of Important Trace Elements in Jordanian Adult Females and Males by Using Atomic Absorption Spectrophotometer - Al-Groom, Rania M.; R. Hamad, Abdul-Wahab; Al-Daline, Saied M. (Pakistan Journal of Nutrition, 2013)
The human body requires certain minerals for the overall health and proper functioning of the organ systems. The essential trace elements were very important for human life, which their imbalance in blood leads to very dangerous diseases (Zn, Cu, Fe, Cr, Se, Co, Mn and Mg). The purpose of this study was to evaluate the concentrations of Zinc, Copper, Iron, Magnesium, Chromium, Selenium, Cobalt and Manganese in serum of healthy adult females and males in Jordan. Serum levels of Zn, Cu, Fe, Mg, Cr, Se, Co, Mn and Mg were determined by flame and flameless atomic absorption spectrophotometer. Blood have been collected from1000 men and 1000 women apparently healthy Jordanian people aged 20-70 years. The mean concentration of zinc was between (0.96-1.02 and 0.8-1.02 μg/mL) in men and women, respectively. The concentration of zinc was slightly increased with ages. The mean values of copper were between (1.38-1.72 μg/mL), there is no significance deficiency in all ages and sexes. The average mean values of Fe were found to be (1.28-1.62 μg/mL) for men and (1.12-1.57 μg/mL) for women, with a deficiency of 5.9% in men and 8.5% in women. The chromium mean in men were between (0.04-0.055 μg/mL) with a deficiency of 43.06%, while in women were between (0.041-0.049 μg/mL), with a deficiency of 40.28%. The concentration of magnesium in blood serum was between 14.2-16.1 μg/mL for men and 14.3-16.3 μg/mL for women. The mean selenium concentrations in all healthy volunteers were in the range of 85-100 ng/mL for men and 82-99 ng/ml for women. The lowest levels of Se were shown in old people. The adult serum Co values were 0-34 ng/mL for men and 0-35 ng/mL for women. The cobalt deficiency was about 17% in men and women. The level of serum Manganese was 14-19 ng/mL for men and 11-15 ng/mL for women, it was noted that the level of Mn in men was higher than in women for all ages. The Mg concentrations of serum were 14.10±3.3 and 14.89±3.3 μg/mL for men and women. On the basis of this study finding and those of other reports, trace elements deficiency may contribute to diets and diseases through its significant effects on various organs parameters. It seems that the estimation of serum or plasma trace elements may help in investigation and treatment of some diseases in both males and females.